G320 Transfer of Ophthalmic services from a Hospital based Eye clinic to Special School Eye clinic for children with special needs. (7th April 2014) - Jmor, F; Ho, V; Farrell, S; Rudduck, G; Gashut, A; Rowlands, A
Abstract : Introduction: Children with moderate to severe learning difficulties find attending Hospital based Eye (HBE) clinics a difficult experience. Long waiting times in a strange, often extremely busy location, coupled with the prospect of eye drops and visual assessment by combinations of optometrists, orthoptists and ophthalmologists, can be daunting. Aims: To assess the "did not attend" (DNA) rate for HBE clinics compared to Special School Eye (SSE) clinics. 2. Establish if parents/carers prefer SSE clinics over current HBE clinics so as to transfer eye services to the community, for this group of children. Methods: Computerised appointment attendance data for children with learning difficulties, who attended three Special Schools from 2010 to date, was retrospectively collated. These children were identified by Community Orthoptists and Optometrists as needing ongoing Ophthalmic assessment. Anonymous questionnaires were also sent to these childrens' parents/carers requesting feedback on their experiences at both HBE and SSE clinics. The questionnaire consisted of a mixture of closed and open-ended questions, focussing on identifying patient demographics in this cohort and drawing comparisons between the HBE and SSE services regarding waiting times, environment, information provided and overall satisfaction with the service. Results: Thirty-nine children were identified as needing ongoing Ophthalmic assessment for either Orthoptic, Optometric or other Ophthalmic issues from three Special Schools. Twenty-four children, aged 6.4 years (mean; range 2 – 10 years) attended both HBE and SSE clinics. Children were known to have a range of conditions with varying severity. The DNA rate for HBE clinics was 54.8% (mean), in comparison to 2.7% (mean) for SSE clinics. Parent/carer satisfaction data indicate significantly higher levels of satisfaction and childrens' compliance on ophthalmic examination with SSE clinics. Conclusions: The high DNA rate at HBE clinics in comparison to SSE clinics and the apparent parent/carer satisfaction with SSE clinics, highlight the evident need for SSE clinics in the region. This may also be a reflection on the rest of the UK, especially for this group of children who often have complex ophthalmic as well as medical and psychosocial needs thus requiring multi-disciplinary input for the most effective management.